Drivers of Corruption : A Brief Review - Søreide, Tina (Washington, DC: World Bank, 2014)
Corruption is motivated by the possibility of securing something of value for oneself and one s allies. The desire to secure benefits is a human trait and generally positive for development; various forms of rewards drive humans to get up in the morning, do a good job, and act responsibly. The discussion now turns to the opportunity to secure more benefits than are entitled to within the existing rules of the game ; specifically, the opportunity to grab at the expense of society. A decision maker has the authority to influence an outcome that matters to the briber. For steering a decision in the briber s direction, the decision maker is compensated with a bribe. The steered decision and the bribe now become assets that usually exceed what at least one of the players would have obtained without the corrupt act. The opportunity to seize assets through some form of power misuse differs across sectors, organizations, and decision-making situations. This chapter describes the circumstances in which the risk of corruption is particularly high in other words, where the drivers of corruption can be found.